Characterization of Nipah virus from naturally infected Pteropus vampyrus bats, Malaysia. - Abd Rahman, Sohayati; Syed Hassan, Sharifah; J. Olival, Kevin; Mohamed, Maizan; Chang, Li Yen; Hassan, Latiffah; Md Saad, Norsharina; A. Shohaimi, Syamsiah; C. Mamat, Zaini; Naim, M. S.; Epstein, Jonathan Harris; Arshad, Siti Suri; et al. (Centers for Disease Control and Prevention, 2010)
We isolated and characterized Nipah virus (NiV) from Pteropus vampyrus bats, the putative reservoir for the 1998 outbreak in Malaysia, and provide evidence of viral recrudescence. This isolate is monophyletic with previous NiVs in combined analysis, and the nucleocapsid gene phylogeny suggests that similar strains of NiV are co-circulating in sympatric reservoir species.